Ethanol extraction from wheat (2009)
Current hike in the price of crude oil in the world market has produced ripples in the economy of nations. Research has therefore been in the area of renewable energy to break the monopoly of fossil fuel. One of such renewable fuels is ethanol. Ethanol has been produced from various feedstock. The objective of this project therefore is to produce ethanol using wheat as the feedstock. Fermentation was carried out to convert glucose (C6H12O6) to ethanol (C2H5OH) and carbon dioxide gas (CO2). 12 liters of fermented mash was heated in the boiler and the first condensate which was 60% water was collected in the receiver between 77°C and 82°C. After discarding the residue in the boiler, the first run distillation was reheated to 95.5° C, when 70% ethanol plus by- products was obtained. This process was repeated a third time. The distillate collected was (E85) i. e. 85% ethanol which was about 170 proof . This ethanol was very flammable.